Strategic decision-making in Olympic bouldering: the role of climbing movement repertoire examined - Henz, J.; Sanchez, X.; Memmert, D.; Medernach, J. P. (International Journal of Sport and Exercise Psychology, 2025)
Bouldering is an Olympic climbing discipline performed on low-height climbing walls, referred to as boulders. Strategic decision-making is an essential, cognitive skill in Olympic bouldering, as climbers have limited time to solve a series of boulders. In developing strategic solutions, climbers draw upon their repertoire of climbing movements, which is conceptualised as high-level knowledge structures stored in long-term memory. Routesetters, those climbers who design and set boulders, possess an extensive movement repertoire, enabling them to create innovative boulders that challenge even highly skilled climbers. This study examined the movement repertoire paradigm as a cognitive system underlying strategic decision-making in Olympic bouldering. We conducted an in situ investigation under ecologically valid conditions by comparing the strategic decision-making skills and bouldering performances of elite climbers with extensive routesetting expertise (RS) to that of elite climbers without such expertise (NR) when tasked with solving an Olympic boulder. Data collection encompassed both strategic and performance-related parameters, including boulder previewing time, decision-making, strategic adjustments, and successful boulder completion. Findings revealed that RS demonstrated superior strategic decision-making, as evidenced by shorter previewing times, higher decision-making scores, fewer strategic adjustments, and were more successful at solving the boulder than NR. Findings provide evidence that routesetting expertise is beneficial for optimising strategic decision-making in Olympic bouldering. The diversity of movements routesetters encounter in their practice expands their movement repertoire. Such an extensive repertoire enables climbers to accurately decode movements and identify specific movement characteristics based on climbing hold configurations, thereby helping them to optimise their strategic decisions.